Renal oncocytoma, benign or malignant - Akhavan, Ali; Binesh, Fariba; Vahedian, Hassan Ali; Bashiri, Hamid Reza; Hakiminia, Marjan (Reports of Radiotherapy and Oncology, 2023)
Introduction: Renal oncocytoma is a benign renal tumor, which is commonly asymptomatic and discovered incidentally with diagnostic imaging. This benign tumor occasionally co-exists with a malignant neoplasm, which may be present within or near the oncocytoma; in addition a few rare cases of renal oncocytoma have simulated a malignant course, showing extension to branches of the renal vein or distant metastasis. Report of the case: A rare case of renal oncocytoma has been reported in a 56 year- old woman, who referred with distant metastatic disease.